IMPLEMENTASI NILAI DEMOKRASI DALAM PENDIDIKAN ISLAM - Adisti Aulia Sudrajat; Hajizah; Sofiata Ria; Ajahari (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2025)
Principle Islamic educational democracy is imbued with the principles of democracy in Islam. This article discusses the importance of educational democracy in the Islamic context, which aims to ensure equal education for all individuals regardless of their for all individuals regardless of background. This research is motivated by the crucial role of education in the humanization and development of individual potential, in line with the goals of national education. The aim is to analyze the implementation of democracy in Islamic education, focusing on the principles of inclusion, participation, justice, and equality. The method used is library research, which involves collecting, analyzing literature research, which involves collecting, analyzing and interpreting data from various written sources. The discussion of this article covers democracy in Islam, the role of Islamic education as a foundation for democratic education, and the implementation of democratic Islamic education through integralistic, humanistic, pragmatic models of education. models of integralistic, humanistic, pragmatic, and culture-based education.